Effect of Work Environment and Work Discipline on Employee Performace at Perumda Tirta Patriot in North Bekasi - Maya Fajarratih; Ari Sulistyowati; Hadita Hadita (Dinasti International Journal of Education Management And Social Science, 2023)
The influence of Work Environment and Work Discipline on Employee Performance at Perumda Tirta Patriot in North Bekasi. This research aims to determine the effect of the Work Environment and Work Discipline at Perumda Tirta Patriot. The method used in this study is a quantitative method, which in this study uses the Probability Sampling technique. The population in this study were all employees of Perumda Tirta Patriot, totaling 133 respondents. Based on the results of the study, it showed that in the partial test (t) the work environment variable had a significant effect on employee performance with a sig value of 0.005 <0.05 and a t-count of 2.870 > table 1.978. And the work discipline variable has a significant effect on employee performance with a sig value of 0.000 <0.05 and a t count of 2.870 > t table 1.978. Furthermore, in the simultaneous test (f) the variables of Work Environment and Work Discipline jointly affect the dependent variable, namely Employee Performance with a sig value of 0.000 <0.05 and an f-count of 283.131 > f-table 3.07. Then for the test of determination (R2), it was found that the correlation between the two variables of Work Environment (X1) and Work Discipline (X2) on Employee Performance (Y) was 81.3%.Based on the identification of the problems that have been described, there are several problems encountered at Perumda Tirta Patriot such as performance, work environment, and work discipline. Other factors besides the work environment, motivation, and work discipline that can significantly impact employee performance, such as competence, organizational culture, workload, and other factors related to improving employee performance, need to be investigated further for further research.